SAT0130 Drug Usage Analysis and Comparative Medication Expenses in Patients with Rheumatoid Arthritis Using Conventional or Biological Therapy. (15th July 2016) - Aza, A.; Cardozo, A.; Santos-Moreno, P.; Villarreal, L.; Ballesteros, G.; Bello, J.; Castillo, E.; Giraldo, R.; Gomez, D.; Lopez, A.; Palacio, N.; Castro, C.; et al.
Abstract : Background: In the last years it has seen a marked improvement in the treatment of rheumatoid arthritis (RA) by using conventional DMARDs and more recently with the introduction of biologics; biological therapy is useful to prevent clinical and radiological progression in patients with RA but is associated with high costs and has impacted budget in Colombian health system. Objectives: The purpose of this study was to assess drug usage of conventional treatment and biologic agents in terms of reduction of the Disease Activity Score 28 (DAS28) and comparative medication expenses associated in patients with moderate-severe RA during a 24 month period. Methods: We conducted a real-world, retrospective, cross-sectional study, based on information from a specialized in RA center in Colombia where there is a model with therapeutic goals like T2T and a multidisciplinary approach. Subjects with moderate-severe disease activity received conventional treatment or biologic therapy, and were followed-up and treated according to DAS28; therapy had to be adjusted with DAS28 >3.2 unless the patient's conditions did not allow it. Descriptive epidemiology was done and the overall drug costs were assessed and compared between the two types of therapies. Results: 526 patients using conventional treatment were included, mean age 63.5 ± 11.8, 424 (80%) female and 102 (20%) male. These patients had a DAS28 on average 4.5 ± 1 at beginning and after 24 months 410 patients (78%) got remission/low disease activity status with a mean DAS28 2.57 ± 1. On the other hand, 303 patients using biologics were included, mean age 58.5 ± 9.4, 251 (82%) female and 52 (18%) male; after 24 months of observation 154 patients (50%) obtained remission/low disease activity status with a mean DAS28 of 2.6 ± 1. Cost of conventional DMARD treatment for RA in Colombia was about 850 US dollars/patient/year because mostly of patients have more than one DMARD; use of biologics cost 7, 725 US dollars/year/patient, ranging between the cheapest biological and the most expensive (4, 878 and 12, 774 US dollars/year respectively); that means conventional treatment is nine times cheaper in comparison with costs of biological therapy and possibly more effective. Conclusions: This study showed that it is possible to decrease disease activity and obtain a significant cost-reduction in treatment of RA by using conventional DMARDs in a model with therapeutic goals like T2T and optimizing a multidisciplinary approach; the use of biologic therapies in the treatment of RA continues being evaluated but is associated with high costs; we show real-world data on drug utilization in patients with moderate-severe RA in a low income developing country. These observations could be used by decision makers in order to consider health decisions; nonetheless, further research based on cost-effectiveness analysis and cost-comparison is needed to verify these results. Disclosure of Interest: None declared